Decline in cognition from mid-life improves specificity of mini-mental state examination: diagnostic test accuracy in Caerphilly Prospective Study (CaPS) - Crevin, S; Fish, M; Bayer, A; Gallacher, J; Ben-Shlomo, Y (IOS Press, 2022)
Background: The merit of using baseline cognitive assessments in mid-life to help interpret cross-sectional cognitive tests scores in later life is uncertain.